The flying machine book : build and launch 35 rockets, gliders, helicopters, boomerangs, and more - Mercer, Bobby, 1961- (Chicago, Ill. : Chicago Review Press, 2012)
"Shows readers how to turn rubber bands, paper clips, straws, plastic bottles, and index cards into amazing, gravity-defying flyers. Each project contains a material list and detailed step-by-step instructions with photos. Mercer also includes explanations of the science behind each flyer, including concepts such as lift, thrust, and drag, the Bernoulli effect, and more"--
Keywords: Paper airplanes; Flying-machines -- Models